ANALYSIS OF THE DEVELOPMENT OF SHARE PRICE OF COMPANIES LISTED ON THE SRI-KEHATI INDONESIA INDEX (CASE STUDY: IMPLEMENTATION OF SDG's) - Farah Dina; Prawidya Hariani RS (Proceeding International Seminar of Islamic Studies, 2022)
This topic was raised based on the phenomena of economic development and environmental sustainability which are contradictory to one another. Various development efforts were carried out for the sake of high economic growth, while the ecological damage caused by excessive exploitation of nature was getting worse. Shares listed on the SRI-KEHATI Index were appointed as research objects because they are a form of implementing SDG's. The main objective of this study is to estimate the factors that influence the stock price of companies listed on SRI-KEHATI, as well as to estimate the effect of these stock prices on production growth. The data used in this study are cross sectional data and panel data. Where the cross-sectional data collected are all companies registered with SRI-KEHATI for 10 consecutive years and the sample was taken in 2017. Meanwhile, the panel data collected is data on all companies registered with SRI-KEHATI for 10 consecutive years and samples were taken from 2009 to 2017. Based on the estimation results using the multiple regression method using E-Views 10 software, in the first model a goodness of fit () value was obtained of 0.999999 or 99.99%. Partially, the independent variables namely PER, EPS, TAT, and BB have a positive and significant effect on stock prices (HS), while the BIF variable has a negative and significant effect on HS. Simultaneously, the independent variables have a positive and significant effect on HS. In the second model, the goodness of fit () value is 0. 001599 or 0.15%. Variable Stock Price (HS) which is influenced by PER, EPS, TAT, BB, and BIF has a positive and not significant effect on Production Growth (PP).